Deletion of a malaria invasion gene reduces death and anemia, in model hosts. - Noé D Gómez; Innocent Safeukui; Aanuoluwa A Adelani; Rita Tewari; Janardan K Reddy; Sam Rao; Anthony Holder; Pierre Buffet; Narla Mohandas; Kasturi Haldar (PLoS ONE)
Malaria parasites induce complex cellular and clinical phenotypes, including anemia, cerebral malaria and death in a wide range of mammalian hosts. Host genes and parasite 'toxins' have been implicated in malarial disease, but the contribution of parasite genes remains to be fully defined. Here we assess disease in BALB/c mice and Wistar rats infected by the rodent malaria parasite Plasmodium berghei with a gene knock out for merozoite surface protein (MSP) 7. MSP7 is not essential for infection but in P. falciparum, it enhances erythrocyte invasion by 20%. In vivo, as compared to wild type, the P. berghei Δmsp7 mutant is associated with an abrogation of death and a decrease from 3% to 2% in peak, circulating parasitemia. The Δmsp7 mutant is also associated with less anemia and modest increase in the size of follicles in the spleen. Together these data show that deletion of a single parasite invasion ligand modulates blood stage disease, as measured by death and anemia. This work is the first to assess the contribution of a gene present in all plasmodial species in severe disease.